ADVANCING SDG 8 THROUGH FINANCIAL INNOVATION: LESSONS FROM DIFFERENT STAGES OF FINANCIAL DEVELOPMENT - Han Hou,; Su-Yin Cheng, (PEOPLE: International Journal of Social Sciences, 2025)
Financial innovation plays a pivotal role in advancing the United Nations' Sustainable Development Goal 8 (SDG 8). The paper explores the dynamic relationship between financial innovation and economic development. The motivation arises from ongoing debates, both theoretical and empirical, about whether financial innovation truly drives long-term economic development. The objective is to evaluate how financial innovation affects real GDP per capita and growth volatility, both in the short and long term, with special attention to countries at different stages of financial development and the role played by the financial crises. Using panel data from 39 countries (1972–2016), the study employs the Pooled Mean Group (PMG) estimator to capture dynamic effects, both pre- and post-crises. The results show that financial innovation fosters long-term economic development but increases growth volatility in highly developed financial systems, particularly before crises. In less developed financial systems, it stimulates growth while increasing volatility both before and after crises. The findings imply that policymakers should carefully regulate financial innovation to ensure that it contributes to long-term growth without exacerbating instability. Most importantly, the study emphasizes the role of financial innovation in achieving SDG 8, which focuses on promoting sustained, inclusive, and sustainable economic growth. It highlights the potential of financial innovation to deliver long-term economic benefits when managed appropriately.